Vocative Intonation in Language Contact: The Case of Bulgarian Judeo-Spanish - Jonas Grünke; Bistra Andreeva; Christoph Gabriel; Mitko Sabev (Languages, 2023)
The present study investigates the prosodic realization of calling contours by bilingual speakers of Bulgarian and (Bulgarian) Judeo-Spanish and monolingual speakers of Bulgarian in a discourse completion task across three pragmatic contexts: (i) neutral (routine) context—calling a child from afar to come in for dinner; (ii) positive context—calling a child from afar to get a present; and (iii) negative (or urgent) context—calling a child from afar for a chastising. Through quantitative analyses of the F0 span between tonal landmarks, alignment of pitch peaks, intensity, and durational and prominence patterns, we systematically account for the phonetic characteristics of the contours and determine their tonal composition and meaning, thereby situating them within the intonation systems of Bulgarian Judeo-Spanish and Bulgarian. It is shown that both languages use the same inventory of contours: (1) L+H* !H-% (the so-called “vocative chant”), (2) L+H* H-L%, and (3) L+H* L-%. However, their distribution differs across contexts and varieties. Monolingual and bilingual speakers of Bulgarian, on the one hand, predominantly use (1) and (2) in neutral and positive contexts and clearly prefer (3) in negative contexts. In Bulgarian Judeo-Spanish, the bilinguals also more often recur to (3) in neutral and positive contexts and generally show more variation.